An Initial Value Problem for Parabolic Monge-AmpOere Equation from Investment Theory (Journal of Partial Differential Equations, 2020)
In this paper the upwind discontinuous Galerkin methods with triangle meshes for two dimensional neutron transport equations will be studied. The stability for both of the semi-discrete and full-discrete method will be proved.